The sixth sense [videorecording (DVD)] - Shyamalan, M. Night; Osment, Haley Joel, 1988-; Collette, Toni; Willis, Bruce, 1955- (Hollywood Pictures Home Video ; Distributed by Buena Vista Home Entertainment, 2000)
A noted child psychologist attempts to help a frightened 8 year-old boy who is experiencing terrifying visions of the dead.